Characterization and distribution of Pseudomonas syringae pv. syrinae on wheat in Syria - Kassem, Mohammad; Nader, Asaad; Kumari, Safaa; Moukahel, Abdulrahman (Phytopathologia Mediterranea, 2022)
Bacterial leaf blight, caused by Pseudomonas syringae, threaten wheat production in many regions. Approximately 500 wheat leaf samples showing symptoms suggestive of bacterial infections were collected from 107 fields in north, central and coastal areas of Syria during the 2021 growing season. Disease symptoms consisted of water soaked dark green to brown lesions on expanding leaves which became necrotic and turned from grey-green to tanwhite. A total of 56 isolates were selected using a semis elective medium, and were characterized further using morphological, biochemical (LOPAT), and pathogenicity tests to identify the virulent properties of isolates, and molecular characterization with PCR using specific primers for the syringomycin production gene. Field observations showed that leaf blight severity was approx. 54%, whereas the coastal area isolates gave high disease severity (61.5%), followed by the central area isolates (56%). The pathogenicity tests showed that all the isolates were pathogenic to wheat under greenhouse conditions, with 63% of ranked as highly virulent. The PCR results confirmed that the isolates were P. syringae pv. syringae. This study increased understanding of the ecology, distribution and severity of the microbial wheat communities in Syria.